Evaluación ex-ante en los sistemas café con sombra y barreras vivas en la subcuenca del Río Cálico, San Dionisio, Matagalpa - Moreno Centeno, N.M.; Calderón Centeno, G. de A.; Gonzalez Rivas, B. Asesor; López, J.A. Asesor (Managua (Nicaragua), 2000)
Sumario (Es, En)
Ilus.; 17 ref.
Tesis (Ing Agr)
Keywords: COFFEA ARABICA; SOMBRA; AGROFORESTERIA; NICARAGUA; SAN DIONISIO; MATAGALPA